2018
DOI: 10.1371/journal.pone.0190819
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and recombination of enterovirus G strains in Japanese pigs: High prevalence of strains carrying a papain-like cysteine protease sequence in the enterovirus G population

Abstract: To study the genetic diversity of enterovirus G (EV-G) among Japanese pigs, metagenomics sequencing was performed on fecal samples from pigs with or without diarrhea, collected between 2014 and 2016. Fifty-nine EV-G sequences, which were >5,000 nucleotides long, were obtained. By complete VP1 sequence analysis, Japanese EV-G isolates were classified into G1 (17 strains), G2 (four strains), G3 (22 strains), G4 (two strains), G6 (two strains), G9 (six strains), G10 (five strains), and a new genotype (one strain)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 54 publications
4
50
0
Order By: Relevance
“…Furthermore, a previous study using reverse genetics revealed that the US EV‐G17‐PLCP strain functionally produces the exogenous PLCP gene in virus‐infected cells, demonstrating its own ALFQ↓GPPV and AEFQ↓GPPT sequences as the putative cleavage sites (Shang et al., ). Considering the sequence similarity of the putative cleavage sites including GPPT−ALFQ, GPPA−ALFQ, and GPPE−ALPQ among global strains (Conceição‐Neto et al., ; Knutson et al., ; Tsuchiaka et al., ), therefore, the cleavage of the inserted PLCP gene appears to be guaranteed using each corresponding cleavage sequence. Consistently, the recombinant ToV‐PLCP of the EV‐G KNU‐1811 strain is bordered by two analogous predicted 3C pro cleavage sites, ALFQ↓GPPV and AVFQ↓GPPT, at its N and C termini, respectively, indicating its proteolytic processing by 3C pro into a functional product (Figure a).…”
mentioning
confidence: 99%
“…Furthermore, a previous study using reverse genetics revealed that the US EV‐G17‐PLCP strain functionally produces the exogenous PLCP gene in virus‐infected cells, demonstrating its own ALFQ↓GPPV and AEFQ↓GPPT sequences as the putative cleavage sites (Shang et al., ). Considering the sequence similarity of the putative cleavage sites including GPPT−ALFQ, GPPA−ALFQ, and GPPE−ALPQ among global strains (Conceição‐Neto et al., ; Knutson et al., ; Tsuchiaka et al., ), therefore, the cleavage of the inserted PLCP gene appears to be guaranteed using each corresponding cleavage sequence. Consistently, the recombinant ToV‐PLCP of the EV‐G KNU‐1811 strain is bordered by two analogous predicted 3C pro cleavage sites, ALFQ↓GPPV and AVFQ↓GPPT, at its N and C termini, respectively, indicating its proteolytic processing by 3C pro into a functional product (Figure a).…”
mentioning
confidence: 99%
“…We call them type 1 recombinant EV-G in this study. Our previous data demonstrated high prevalence of type 1 recombinant EV-G in the EV-G population (Tsuchiaka et al, 2018). Our previous data demonstrate high https://doi.org/10.…”
mentioning
confidence: 82%
“…Overlapping PCR of type 2 recombinant EV-G. RNAs were re-extracted in this study from the pig feces using High Pure Viral Nucleic Acid Kit (Roche), and cDNA was synthesized with random primers using SuperScript III First-Strand Synthesis System (Invitrogen), as described previously (Tsuchiaka et al, 2018). Primers for PCR (Table 1) were designed to amplify the viral genome at approximately every 1 kb with overlap regions.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations